Fibula Free Flap for Mandible Reconstruction: Analysis of 30 Consecutive Cases and Quality of Life Evaluation - Maciejewski, Adam; Szymczyk, Cezary (Journal of Reconstructive Microsurgery, 2007)
Accepted: May 4, 2006The objectives of this study were to evaluate the use of fibula free flaps (FFF) for mandible reconstruction in patients with oral cavity cancer and to assess the quality of life (QOL) of the patients who underwent reconstructive surgery. Thirty patients with T3, T4 oral cavity carcinoma underwent surgical resection of the primary tumor infiltrating the mandible or primarily originating from the mandible. According to the length (less or more than 8 cm) and localization (anterior or posterior) of the mandibular defect, patients were subdivided into four groups. In all cases an osseoseptocutaneous FFF was chosen for postresective defect reconstruction. To reconstruct anterior mandibular defects, two osteotomies were needed to give the fibula a proper shape. For extended defects, the fibula usually required more than one osteotomy. Skin islands were designed based on Doppler cutaneous perforator findings. The fibular free skin islands remained viable in all patients and no partial or total skin loss was observed. In the majority of patients (87percent) the facial artery was used for arterial anastomosis. In 6 month follow-ups, the QOL was evaluated as very good except for socioeconomic items. Pain was mild and incidental. Appearance and subjective feeling scores were excellent in two groups with mandibular defects smaller than 8 cm, although in patients with larger defects, they were still very good. Functional effects remained good, and they correlated with the size of defects. In contrast, social activities, recreation, and employment were below patients' expectations and generally reflected the current situation in Poland, but no correlation with the results of reconstruction was found. The present results show that osseocutaneous fibula free flap used in reconstructive surgery for cancer of the oral cavity allows more radical and aggressive resection with very good or excellent functional and aesthetic outcome. Estimated QOL seems an important part of evaluation of the treatment outcome.
Keywords: Oral cavity cancer; fibula free flap; reconstructive surgery; QOL evaluation